Trends and hotspots in global influenza and intestinal flora research based on bibliometrics - Wu, Dongsheng; Wang, Tongtong; Wu, Haoran; Dong, Yuang; Huang, Ziqin; Zhang, Jun; Zhang, Wei (Frontiers in Microbiology, 2025)
ObjectiveInfluenza (hereinafter referred to as influenza) is a pandemic and seasonal respiratory infectious disease that can lead to a global pandemic, posing a major threat to global public health. Studies have shown that influenza can lead to an imbalance in the intestinal flora, and disruption of the intestinal flora can exacerbate the progression of the disease, suggesting a potential link between influenza and intestinal flora. There is still a lack of systematic summary of bibliometric analysis in this field, therefore, this study aims to reveal the research dynamics, collaborative networks and cutting-edge hotspots in the field of influenza-intestinal flora association through bibliometric methods.MethodsBibliometric analysis was used to retrieve 554 papers on influenza and intestinal flora from the Web of Science Core Collection (WoSCC) database from 2011 to 2025. After screening, 283 papers were included, and co-occurrence and clustering analyses of countries, authors, institutions, journals, references, and keywords were performed using VOSviewer, CiteSpace, and Bibliometrix; statistical visualization was performed via Microsoft Excel.ResultsChina is the country with the highest number of published papers and the leading CSI in terms of international collaboration intensity. The most popular journal in this field is Frontiers in Microbiology with 20 publications, while the most influential journal is Nature with 605 citations. Zhejiang University was the institution with the highest number of publications and Francois Trottein was the most prolific author. Keyword co-occurrence analysis showed that gut microbiota, influenza, probiotics, intestinal microbiota and COVID-19 were the core research hotspots, and clustering analysis further revealed the “intestinal-pulmonary axis of immunoregulation,” such as Cluster analysis further revealed the “intestinal-lung axis immunoregulation,” such as Th17/Treg balance, short-chain fatty acids and probiotics, as the cutting edge.ConclusionThis study is the first to systematically map the bibliometrics of influenza and gut flora. The most influential countries, research institutions and researchers were identified through bibliometric analysis, showing the current research trends and hotspots in influenza and intestinal flora control. The results can provide theoretical guidance for future influenza prevention and control strategies targeting flora.